Creating Multimodal Texts Online to Improve Young Adults’ English Skills at Two State Institutions - Galvis Pinzón, Diana Pahola; Callejas, Linda Lucia (Universidad Pedagógica y Tecnológica de Colombia, 2017)
This paper aims to describe the creation of multimodal texts as a pedagogical strategy implemented through the use of ICT tools in two state institutions in the Colombian province of Santander. After analyzing teaching practices, it was observed that written texts were usually approached in a linear manner without taking into consideration other text modes, which may lead students to lose interest in literacy practices. Accordingly, an action research was conducted following a qualitative paradigm based on a descriptive-interpretative methodology. The research results suggested learner improvement resulting from the use of ICT for educational purposes, learning English through the implementation of integrated skills, and working collaboratively. It was also concluded that when creating multimodal texts, it is important to bear in mind both: students’ perceptions of the world and the role of the teacher as a facilitator of ICT tools for academic purposes in virtual learning environments.